2021
DOI: 10.1111/jfbc.13899
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic effects of space‐induced Lactobacillus plantarum SS18‐5 on type 2 diabetes in a rat model

Abstract: Probiotics can improve dyslipidemia and promote metabolic control as a therapeutic approach for type 2 diabetes mellitus (T2DM). The hypoglycemic effects of space‐induced Lactobacillus plantarum SS18‐5 on T2DM were explored in 4‐week‐old male Sprague Dawley rats. The normal (N) group was fed a basal diet, while the other groups received a high glucose fat diet. T2DM was established by streptozotocin injection and the T2DM rats were randomly divided into three groups, a diabetic (D) group (T2DM rats treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…It has been suggested that supplementation with probiotics has potential for improving type 2 diabetes, because probiotics are hypoglycemically active. For example, treatment with L. plantarum SS18–5 markedly improved the blood glucose of, and diminished oxidative stress in, diabetic rats [ 38 ]. Zhong et al substantiated the protective activity of L. plantarum ZJUFB2 from insulin resistance via modulating enteric microbiota and bile acids in HFD-treated mice [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that supplementation with probiotics has potential for improving type 2 diabetes, because probiotics are hypoglycemically active. For example, treatment with L. plantarum SS18–5 markedly improved the blood glucose of, and diminished oxidative stress in, diabetic rats [ 38 ]. Zhong et al substantiated the protective activity of L. plantarum ZJUFB2 from insulin resistance via modulating enteric microbiota and bile acids in HFD-treated mice [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study, among obese rats ( n = 15), showed that probiotic supplements Lactobacillus acidophilus and Lactiplantibacillus plantarum , when administered orally, were effective in reducing the weight of obese rats. In addition, Lactiplantibacillus plantarum was proven effective in weight loss in Yang et al’s [ 71 ] research. In a similar vein of DM physiochemical parameters improvement was Hsieh et al’s [ 12 ] research among 50 DM rats, orally administered Liquorilactobacillus salivarius , Lactobacillus johnsonii , Limosilactobacillus reuteri , and Bifidobacterium animalis subsp.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have successfully applied space mutagenesis to improve the health-promoting effects of probiotic bacteria. For example, a space-exposed mutant, Lactiplantibacillus plantarum SS18-5, has shown effective hypoglycemic effects on type 2 diabetes in a rat model ( 14 ). Another space-exposed mutant, Limosilactobacillus reuteri F-9-35, has been found to enhance anti-gastric injury and anticolitis effects in rats ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%